Perancangan Aplikasi SPK Penerimaaan Tenaga Kerja Honorer dengan Menggunakan Metode MAUT - Putri, Kirana Dwi; Juledi, Angga Putra; Munthe, Ibnu Rasyid (LPPM UNIKA Santo Thomas Medan, 2023)
The Plantation Service is the implementing element of the Provincial Government, led by a Head of Service, located under and responsible to the Regional Head through the Regional Secretary. The Plantation Service has the task of carrying out the authority of the Provincial Government and the task of Deconcentration in the plantation sector. According to Government Regulation No. 48 of 2005 as amended by Government Regulation No. 56 of 2012, an honorary employee is someone who is appointed by a staffing officer in a government agency to carry out certain tasks. Planning for the needs of honorary workers is part of the activities of preparing a recruitment program to select and obtain qualified workers in an agency. However, in the recruitment process for honorary workers at the North Sumatra Plantation Service, too many applicants and application files as well as the lengthy selection stages make it difficult for an agency to find new honorary workers, as desired. Therefore, the role of a decision support system is needed in overcoming the problems faced today. Therefore, to determine prospective honorary workers, a decision support system is needed to facilitate work and avoid errors in calculating system data quickly and more accurately by using the Multi Attribute Utility Theory (MAUT) method. From the results of this study, the MAUT method produced the best preference value of 0.493 on behalf of Sarah, S.E as the first rank